Comparison of Wound Infection in Uncomplicated Acute Appendicitis by Subcuticular Suture and Interrupted Suture - Zarei, Farshad; Ahmadinejad, Mojtaba (Infectious Disorders - Drug Targets, 2021)
Background: Postoperative complications such as wound infection and scarring are some of the major concerns regarding suturing techniques. This study is designed to evaluate postoperative outcomes of adhering subcuticular sutures in comparison to the interrupted suturing method in patients who underwent appendectomy for uncomplicated acute appendicitis. Methods: 240 patients were randomly assigned into two groups; 120 with interrupted and 120 subcuticular sutures after an appendectomy, at Shohada Ashayer hospital, Khorramabad, Iran. The prevalence of wound infection, three days after the surgery in the hospital and a week after discharge was determined and evaluated statistically. Results: No wound infection was seen within three days of hospitalization in the subcuticular group whereas, 1 patient reported infection in the interrupted group, however, the difference was not statistically significant. A week after discharge, a patient was reported to have wound infection in the subcuticular group and 2 in the interrupted group. No significant difference was seen in this regard either. 55 females and 66 males received subcuticular sutures whereas, 74 males and 46 females were given interrupted sutures for wound closing. One male in interrupted and 1 male and female in the subcuticular group were referred for wound infection, after discharge, respectively. Among these groups, no significant differences were seen. In catarrhal appendicitis, the infection was reported in the interrupted group only which was not statistically significant. Conclusion: Subcuticular sutures provide better cosmetic outcomes without any additional complications in comparison to interrupted sutures.
Keywords: Wound infection